Pengaruh kepribadian wirausaha, pengetahuan kewirausahaan, dan lingkungan terhadap minat berwirausaha siswa SMK - Eka Aprilianty (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2012)
Tujuan penelitian untuk mengungkapkan pengaruh potensi kepribadian wirausaha, pengetahuan kewirausahaan, dan lingkungan keluarga terhadap minat berwirausaha. Penelitian menggunakan pendekatan ex post facto. Populasi adalah siswa SMK Rumpun Pertanian di Daerah Istimewa Yogyakarta. Sampel sebanyak 113 responden ditentukan menggunakan teknik proportional random sampling. Data dikumpulkan dengan instrumen angket dan tes. Analisis data menggunakan statistik deskriptif dan statistik inferensia. Penelitian menunjukkan minat berwirausaha relatif rendah (48,67%), potensi kepribadian wirausaha memberi pengaruh cukup berarti terhadap minat berwirausaha (27,3%), pengetahuan kewirausahaan berpengaruh berarti terhadap minat berwirausaha (13,7%), lingkungan keluarga memberi pengaruh yang berarti terhadap minat berwirausaha (22%). Terdapat pengaruh secara bersama-sama antara potensi kepribadian wirausaha, pengetahuan kewirausahaan, dan lingkungan keluarga sebesar 42,2 persen terhadap minat berwirausaha. THE EFFECT OF ENTREPRENEUR PERSONALITY, ENTREPRENEURSHIP KNOWLEDGE, AND ENVIRONMENT ON ENTREPRENEURIAL INTEREST OF VOCATIONAL HIGH SCHOOL STUDENTSAbstractThe Effect of Potential Entrepreneur Personality, Entrepreneurship Knowledge, and Environment on Entrepreneurial Interest of Vocational High School Students. The purposes of this research are to reveal the effect of potential entrepreneur personality, entrepreneurship knowledge, and environment on the entrepreneurial interest. This study uses the ex post facto approach. The population is Agriculture vocational high school students in Daerah Istimewa Yogyakarta. A sample of 113 respondents is established using the proportional random sampling technique. The data are collected using questionnaires and a test. The data are analyzed using descriptive statistics and statistical inference. The results show that almost half (48.67) of students have a low entrepreneurial interest. The results also show that potential entrepreneur personality gives a positive and significant effect on entrepreneurial interest (27.3%). Entrepreneurship knowledge has a significant positive effect on entrepreneurial interest (13.7%). Family environment has a significant positive effect on entrepreneurial interest (22%). The potential entrepreneur personality, entrepreneurship knowledge, and family environment collectively have the effect of 42.2 percent on the entrepreneurial interest.